A water-based lignin-based epoxy resin coating and preparation method thereof

By extracting lignin from coffee grounds and epoxy modification in a uniform solution, the problems of low lignin reactivity and epoxy grafting rate in the prior art are solved, and the high resistance of epoxy resin coatings is achieved UV performance and long service life, and achieve environmentally friendly, low-cost high added value utilization coffee grounds.

CN119019935BActive Publication Date: 2025-02-18GUANGDONG TUOPU SYNTHETIC TECH CO LTD
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202411505044.X
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-10-28
Publication Date
2025-02-18
Estimated Expiration
2044-10-28

AI Technical Summary

Technical Problem

The prior art is difficult to improve the reactivity of lignin and the grafting rate of epoxy groups without destroying the natural properties of lignin, thereby improving the ultraviolet resistance and service life of epoxy resins.

Method used

By extracting lignin from coffee grounds, a uniform and stable solution is formed, and cyclopropyl is grafted on phenolic hydroxyl groups by aldehyde hydrolysis, and finally oxidizing cyclopropyl to epoxy group, the preparation of epoxy modified lignin is achieved. . This method performs homogeneous reaction in a uniform solution, which improves the reactivity of lignin groups while retaining the natural UV resistance of lignin.

Benefits of technology

The high epoxy content and UV resistance of epoxy resin coatings have been improved, the service life of epoxy resins has been extended, and a way to utilize coffee grounds with an environmentally friendly, low-cost and high added value are provided.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119019935B_ABST
    Figure CN119019935B_ABST
Patent Text Reader

Abstract

The invention discloses a water-based lignin-based epoxy resin coating and a preparation method thereof, and belongs to the field of high value-added utilization of biomass resources and epoxy resin cross technology. The raw materials of the water-based lignin-based epoxy resin coating are: 30-50 parts of epoxy modified lignin, 10-20 parts of epoxy polymer, 8-12 parts of epoxy resin curing agent, 0.020-0.030 parts of epoxy resin accelerator, 4-6 parts of emulsifier, 10-20 parts of diluent, 0.5-0.8 parts of defoamer and 80-100 parts of deionized water by weight; the preparation method of the epoxy modified lignin includes pretreatment, cyclopropyl modification of lignin, collection and purification of cyclopropyl modified lignin, and epoxy modification of lignin. The present invention utilizes organic aldehyde acid with high reaction activity with lignin to carry out grafting reaction, further oxidizes cyclopropyl group into epoxy group, and successfully grafts epoxy group into lignin molecular chain. This method has high epoxy grafting rate, and at the same time will not destroy the natural structure of lignin, and retains its original anti-ultraviolet performance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of high value-added utilization of biomass resources and epoxy resin cross technology, and in particular relates to a water-based lignin-based epoxy resin coating and a preparation method thereof. Background Art

[0002] Coffee is one of the three major beverages in the world. Between 2000 and 2012, global coffee production increased by nearly 17%. According to the International Coffee Organization, the global coffee industry processed about 9.6 million tons in 2017. In the coffee production steps such as roasting and brewing, more than 90% of the initial dry coffee mass is produced in the form of coffee grounds. The waste generated from coffee in coffee-producing countries accounts for more than 50% of the total fruit residues. Therefore, coffee grounds are a kind of agricultural and forestry waste with huge output. For this reason, coffee factories need to spend a certain cost to treat coffee grounds. The composition of coffee grounds is relatively complex, mainly including lignin, cellulose, hemicellulose and lipids, as well as a small amount of protein, polyphenols and minerals. The lignin content is about 30wt%, and the total content of cellulose and hemicellulose is about 40~50wt%. Resource utilization of coffee grounds can not only reduce the pollution of coffee grounds to the environment, but also bring certain economic benefits.

[0003] Coffee grounds contain a large amount of lignin, with a dry weight ratio of about 18~33 wt%. As a natural polymer, lignin contains a large number of active groups, such as aromatic groups, phenolic hydroxyl groups, alcoholic hydroxyl groups, carbon-based conjugated double bonds, etc. These active groups can undergo oxidation, reduction, hydrolysis, alcoholysis, acidolysis, methoxyl groups, carboxyl groups, photolysis, phthalidation, sulfonation, alkylation, halogenation, nitration, polycondensation or graft copolymerization and many other chemical reactions. At the same time, these groups can absorb a large amount of ultraviolet rays in sunlight and convert the absorbed ultraviolet rays into infrared waves for reflection, so that lignin has excellent anti-ultraviolet properties.

[0004] Epoxy resin is a kind of high molecular polymer, which refers to a general term for a class of polymers containing two or more epoxy groups in the molecule. Due to the chemical activity of epoxy groups, a variety of compounds containing active hydrogen can be used to open the ring, solidify and cross-link to form a network structure. Among them, bisphenol A epoxy resin has the largest output and the most complete variety, and new varieties of this type are still increasing, and the quality is constantly improving. However, long-term exposure of epoxy resin to sunlight, especially ultraviolet rays in sunlight, will promote the oxidation of epoxy groups and produce colored substances, which seriously affects the service life of epoxy resin. Therefore, it is urgent to develop an epoxy resin that is UV-resistant and long-term stable under sunlight.

[0005] Imparting the anti-ultraviolet property of lignin to epoxy resin is a new idea for producing anti-ultraviolet epoxy resin. Among them, Chinese patent [CN202011027011.0] discloses a waterproof lignin-based epoxy resin adhesive, especially a method for preparing an oleyl lignin-based epoxy resin, comprising the following steps: (1) adding lignin and N,N-dimethylformamide to a container, stirring at 20-80 °C for 2 hours, then adding catalyst A, mixing evenly, then adding oleyl chloride, and reacting at 40-70 °C for 1-3 hours; (2) adding epichlorohydrin and catalyst B to the reaction system in step (1), stirring and reacting at 20-80 °C for 2-8 hours, and obtaining an oleyl lignin-based epoxy resin. This patent uses lignin as a raw material and directly grafts epoxy groups onto the molecular chain of lignin. However, the molecular weight of lignin is relatively large, resulting in low reactivity of the functional group, and it also has a large steric hindrance, which makes the grafting rate of epoxy groups relatively low.

[0006] To solve the above problems, Chinese patent [CN201811314354.8] discloses a method for modifying lignin, comprising the following steps: adding lignin and metal oxide to a low eutectic for modification reaction, and after the reaction is completed, separating to obtain modified lignin. Based on the modification method of lignin, the invention also provides a method for preparing a lignin-based epoxy resin. The modification method of lignin of the invention uses a low eutectic as a solvent, cooperates with metal oxides to modify lignin, and uses urea and choline chloride in the low eutectic to form hydrogen bonds to controllably break CC, CO bonds and surface functional groups in the lignin structure, so as to achieve the effect of fully dissolving lignin, and then uses the lattice oxygen formed in the M=O bond of the metal oxide to selectively oxidize lignin, thereby efficiently catalyzing the removal of methoxy groups on the surface of lignin and breaking CO bonds in lignin, thereby achieving the purpose of reducing the steric hindrance of the spatial structure of lignin and increasing the surface hydroxyl content, and can improve the reactivity of lignin with epichlorohydrin. This patent breaks the molecular chain of lignin and converts it into three monomers of lignin, thereby increasing the grafting rate of epoxy groups. However, the destruction of the molecular chain of lignin will destroy or even eliminate the natural properties of lignin.

[0007] Therefore, it is urgently needed to develop a method to improve the reaction activity of lignin, promote the grafting rate of epoxy groups, while retaining the natural properties of natural lignin, such as UV resistance, and use epoxy-modified lignin as an epoxy resin raw material to improve the UV resistance of epoxy resin. Summary of the invention

[0008] The object of the present invention is to provide a water-based lignin-based epoxy resin coating and a preparation method thereof, wherein lignin is extracted from a biomass material, i.e., coffee grounds, to form a uniform and stable solution, and then a cyclopropyl group is successfully grafted onto a phenolic hydroxyl group by aldehyde hydrolysis, and finally the cyclopropyl group is oxidized to an epoxy group, such as Figure 1 As shown, the homogeneous reaction in a uniform solution not only improves the reactivity of the lignin group, but also does not cause a large amount of damage to the lignin molecular chain, thereby retaining the natural properties of the lignin. The prepared epoxy-modified lignin is used as the raw material of epoxy resin, giving the epoxy resin coating an anti-ultraviolet property and extending the service life of the epoxy resin.

[0009] The specific technical solutions are as follows

[0010] A water-based lignin-based epoxy resin coating, wherein the raw materials of the water-based lignin-based epoxy resin coating are, by weight, 30-50 parts of epoxy-modified lignin, 10-20 parts of epoxy polymer, 8-12 parts of epoxy resin curing agent, 0.020-0.030 parts of epoxy resin accelerator, 4-6 parts of emulsifier, 10-20 parts of diluent, 0.5-0.8 parts of defoamer and 80-100 parts of deionized water; the preparation method of the epoxy-modified lignin comprises the following steps:

[0011] S1 pretreatment: Soak the coffee grounds in n-hexane with a mass volume ratio of 5-10 g of coffee grounds to n-hexane: 1-10 mL, react at 20-30 °C and a mechanical stirring speed of 200-500 rpm for 3-6 hours, filter and remove the filtrate to obtain the coffee grounds after impurities are removed;

[0012] S2 Cyclopropyl modification of lignin: add 20-30 parts of coffee grounds treated with S1, 35-45 parts of cyclopropyl hydrocarbon aldehyde, 35-45 parts of 1,4-dioxane and 2-5 parts of hydrochloric acid to a multifunctional reactor in order by mass to obtain a reactant, heat the reactant to 90-100 °C at a stirring speed of 500-1000 rpm, react for 2-4 hours, stir every 30 minutes until the reaction is completed; filter, then wash with 1,4-dioxane and methanol in turn until the washing liquid is colorless to ensure that the cellulose is completely removed, collect the filter residue, dry it, and obtain crude cyclopropyl modified lignin;

[0013] S3 Collection and purification of cyclopropyl modified lignin: The crude cyclopropyl modified lignin obtained in S2 is added to a multifunctional reactor, and 1,4-dioxane and cyclopropyl aldehyde are added in sequence, and then a NaHCO3 solution is added to neutralize the acid in the filter residue; then, the mixture is heated to 30-40°C and the pressure is 55-65 mbar by vacuum distillation to distill out 1,4-dioxane and collect and store it, the distilled solution is filtered, the filter residue is collected, and the filter residue is air-dried at 30°C to obtain purified cyclopropyl modified lignin; the mass ratio of crude cyclopropyl modified lignin, 1,4-dioxane and cyclopropyl aldehyde is 10:20-30:6-8;

[0014] S4 Epoxy modification of lignin: Add the purified cyclopropyl-modified lignin obtained in S3 into a multifunctional reactor, add hydrogen peroxide with a concentration of 10 wt%~30 wt%, then add sodium hydroxide, adjust the pH value of the reaction solution to 10~12, heat to 50~60°C, reflux for 3~5 hours, filter, wash with deionized water until the washing solution is neutral, collect the filter residue, and obtain epoxy-modified lignin; the mass ratio of the purified cyclopropyl-modified lignin to hydrogen peroxide is 1:3~9.

[0015] In some embodiments, the cyclopropyl hydrocarbon aldehyde in S2 is at least one of cyclopropyl acetaldehyde, cyclopropyl propionaldehyde, and cyclopropyl butyraldehyde.

[0016] In some embodiments, the cyclopropyl hydrocarbon aldehyde in S3 is at least one of cyclopropyl acetaldehyde, cyclopropyl propionaldehyde, and cyclopropyl butyraldehyde.

[0017] In some embodiments, the epoxy polymer is at least one of bisphenol A epoxy resin, glycerol epoxy resin, and butylene epoxy resin.

[0018] In some embodiments, the epoxy resin curing agent is at least one of methyl polyethylene glycol amine, ethylenediamine, hexamethylenediamine, diethylaminopropylamine, dicyandiamide, and phthalic anhydride.

[0019] In some embodiments, the epoxy resin accelerator is at least one of DMP-30, triethylamine, triethanolamine, phenol, and resorcinol.

[0020] In some embodiments, the diluent is at least one of alkylene glycidyl ether, 1,4-butanediol diglycidyl ether, ethylene glycol diglycidyl ether, polypropylene glycol diglycidyl ether, 1,6-hexanediol diglycidyl ether, neopentyl glycol diglycidyl ether, and hexanediol diglycidyl ether.

[0021] In some embodiments, the emulsifier is at least one of epoxy resin emulsifier ZJ-203 and epoxy resin emulsifier BY-3052.

[0022] In some embodiments, the defoaming agent is at least one of polysiloxane, GP-type glycerol polyether, and ethylene glycol siloxane.

[0023] The present invention also provides a method for preparing a water-based lignin-based epoxy resin coating, and the preparation method comprises the following steps:

[0024] a. In a multifunctional reactor, deionized water, epoxy-modified lignin, epoxy polymer and diluent are added in sequence according to the formula weight, nitrogen is introduced, and stirring is performed at a speed of 300-800 rpm for 10-30 minutes, then an emulsifier is added, the temperature is raised to 80-100 °C, stirring is continued at the same speed for 30-60 minutes to form a stable emulsion, the temperature is lowered to 40-50 °C, a defoamer is added, stirring is performed at a stirring speed of 1000-2000 rpm for 10-30 minutes, and the introduction of nitrogen is stopped;

[0025] b. Continue to add epoxy resin curing agent and epoxy resin accelerator according to the formula amount, stir at a stirring speed of 500-1000 rpm for 10-30 minutes, then heat to 80-100 ° C, react for 6-10 hours, during which time use a water separator to remove water vapor generated by evaporation. After the reaction is completed, cool to 40-60 ° C, stir at a stirring speed of 3000-5000 rpm for 30-60 minutes, and then stir at a stirring speed of 300-500 rpm for 30-60 minutes to obtain the water-based lignin-based epoxy resin coating.

[0026] The present invention has the following advantages:

[0027] (1) Using coffee grounds, a byproduct of the coffee industry, as production raw materials has low costs and can reduce the pollution of coffee grounds to the environment, achieving high-value utilization of waste, and providing a new way to utilize coffee grounds;

[0028] (2) The present invention utilizes organic aldehyde acid with high reactivity with lignin to carry out grafting reaction, further oxidizes the cyclopropyl group into epoxy group, and successfully grafts the epoxy group into the lignin molecular chain. This method has a high epoxy grafting rate, and at the same time does not destroy the natural structure of lignin, retaining its original anti-ultraviolet performance;

[0029] (3) The epoxy-modified lignin provided by the present invention has a high epoxy content, and the maximum epoxy content can reach 0.98 mol / 100 g, which is convenient for the subsequent epoxy addition reaction to form a three-dimensional network structure. Combined with the high molecular weight of lignin, the mechanical strength of the epoxy resin film after film formation is high;

[0030] (4) Introducing lignin with anti-ultraviolet properties into epoxy resin can give the epoxy resin anti-ultraviolet properties, improve the stability of the epoxy resin, extend the service life of the epoxy resin, and expand the application field of the epoxy resin. BRIEF DESCRIPTION OF THE DRAWINGS

[0031] Figure 1 is the chemical equation for the reaction between organic aldehyde acid and lignin;

[0032] Figure 2 The scanning electron microscope images of the untreated coffee grounds and the coffee grounds after the pretreatment of Examples 1 to 3 are shown;

[0033] Figure 3 The infrared spectra of the cyclopropyl-modified lignin and the epoxy-modified lignin prepared in Examples 4 to 9;

[0034] Figure 4 The UV-visible-near infrared absorption spectra of the water-based lignin-based epoxy resin films prepared in Examples 10 to 15;

[0035] The chemical molecular structure of R1 can be: , , ;

[0036] The chemical molecular structure of R2 can be: , , . DETAILED DESCRIPTION

[0037] The following will be combined with the drawings, technical process steps, specific implementation conditions and materials in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0038] Example 1

[0039] The coffee grounds purchased from the market were characterized by scanning electron microscopy, such as Figure 2 As shown in a, the surface has a small amount of pores filled with organic substances. Coffee grounds were soaked in n-hexane, with a mass volume ratio of coffee grounds to n-hexane of 5 g:1 mL. The mixture was reacted at 30 °C and a mechanical stirring speed of 500 rpm for 6 hours. The filtrate was filtered to remove impurities and the coffee grounds were characterized by scanning electron microscopy. Figure 2 As shown in middle b, the results show that the surface of the treated coffee grounds has a rich pore structure and a large amount of organic matter has been removed.

[0040] Example 2

[0041] Coffee grounds were soaked in n-hexane with a mass volume ratio of coffee grounds to n-hexane of 7 g:7 mL. The mixture was stirred at 25 °C for 4 hours at a mechanical stirring speed of 300 rpm. The filtrate was filtered to remove impurities from the coffee grounds. The coffee grounds were characterized by scanning electron microscopy. Figure 2 As shown in middle c, the results show that the surface of the treated coffee grounds has a rich pore structure and a large amount of organic matter has been removed.

[0042] Example 3

[0043] Coffee grounds were soaked in n-hexane with a mass volume ratio of coffee grounds to n-hexane of 10 g:10 mL. The mixture was stirred at 20 °C for 3 hours at a mechanical stirring speed of 200 rpm. The filtrate was filtered to remove impurities from the coffee grounds. The coffee grounds were characterized by scanning electron microscopy. Figure 2 As shown in middle d, the results show that the surface of the treated coffee grounds has a rich pore structure and a large amount of organic matter has been removed.

[0044] Example 4

[0045] Into the multifunctional reactor, 20 parts of coffee grounds treated in Example 1, 35 parts of cyclopropylacetaldehyde, 35 parts of 1,4-dioxane and 2 parts of hydrochloric acid were added in order by mass. The reactants were heated to 100° C. at a stirring speed of 1000 rpm, and the reaction was carried out for 4 hours. The reaction solution was stirred every 30 minutes until the reaction was completed; the mixture was filtered, and then washed with 1,4-dioxane and methanol in turn until the washing liquid was colorless to ensure that the cellulose was completely removed, and the filter residue was collected and dried to obtain crude cyclopropyl modified lignin. The obtained crude cyclopropyl modified lignin was added into a multifunctional reactor, and 1,4-dioxane and cyclopropylacetaldehyde were added in sequence, and then NaHCO3 solution was added to neutralize the acid in the filter residue, wherein the mass ratio of crude cyclopropyl modified lignin, 1,4-dioxane and cyclopropylacetaldehyde was 10:20:6; then, the mixture was heated to 30°C and the pressure was 55 mbar to perform distillation, 1,4-dioxane was evaporated and collected and stored, the distilled solution was filtered, the filter residue was collected, and the filter residue was air-dried at 30°C to obtain purified cyclopropyl modified lignin, which was characterized by infrared spectroscopy as shown in the following figure: Figure 3 As shown in a, there is no obvious infrared absorption at the characteristic peak 912 and the -CO- bond, while there is a strong absorption at the characteristic peak 3426, i.e. -CH2-, indicating that the cyclopropyl modification is successful.

[0046] The cyclopropyl modified lignin obtained above was added into a multifunctional reactor, and hydrogen peroxide with a concentration of 10 wt% was added, and the mass ratio of cyclopropyl modified lignin to hydrogen peroxide was 1:3. Then sodium hydroxide was added, and the pH value of the reaction solution was adjusted to 10. The mixture was heated to 60 °C and refluxed for 5 hours. The mixture was filtered and washed with deionized water until the washing solution was neutral. The filter residue was collected to obtain epoxy modified lignin. The obtained epoxy modified lignin was characterized by infrared spectroscopy. Figure 3 As shown in b, at the characteristic peak 912, there is an obvious infrared absorption, and at the characteristic peak 3426, there is a strong absorption of -CH2-, indicating that the epoxy modification is successful. The epoxy equivalent of the epoxy-modified lignin obtained by further testing with the hydrochloric acid-pyridine method is 0.84 mol / 100 g.

[0047] Example 5

[0048] Into the multifunctional reactor, 25 parts of coffee grounds treated in Example 2, 40 parts of cyclopropylacetaldehyde, 40 parts of 1,4-dioxane and 4 parts of hydrochloric acid were added in order by mass. The reactants were heated to 95° C. at a stirring speed of 700 rpm, and reacted for 3 hours. The reaction solution was stirred every 30 minutes until the reaction was completed; filtered, and then washed with 1,4-dioxane and methanol in turn until the washing liquid was colorless to ensure that the cellulose was completely removed, and the filter residue was collected and dried to obtain crude cyclopropyl modified lignin. The obtained crude cyclopropyl modified lignin was added into a multifunctional reactor, and 1,4-dioxane and cyclopropylacetaldehyde were added in sequence, the mass ratio of cyclopropyl modified lignin, 1,4-dioxane and cyclopropylacetaldehyde was 10:25:7, and then NaHCO3 solution was added to neutralize the acid in the filter residue; then the vacuum distillation was heated to 35 °C and the pressure was 60 mbar to distill, 1,4-dioxane was evaporated and collected and stored, the distilled solution was filtered, the filter residue was collected, and the filter residue was air-dried at 30 °C to obtain the purified cyclopropyl modified lignin, which was characterized by infrared spectroscopy as shown in the following figure: Figure 3 As shown in a, there is no obvious infrared absorption at the characteristic peak 912 and the -CO- bond, while there is a strong absorption at the characteristic peak 3426, i.e. -CH2-, indicating that the cyclopropyl modification is successful.

[0049] The cyclopropyl modified lignin obtained above was added into a multifunctional reactor, and hydrogen peroxide with a concentration of 20 wt% was added, and then sodium hydroxide was added, and the pH value of the reaction solution was adjusted to 11, heated to 55 °C, refluxed for 4 hours, filtered, washed with deionized water until the washing solution was neutral, and the filter residue was collected to obtain epoxy modified lignin; the mass ratio of the cyclopropyl modified lignin to the hydrogen peroxide was 1:6, and the obtained epoxy modified lignin was characterized by infrared spectroscopy as follows Figure 3As shown in b, at the characteristic peak 912, there is an obvious infrared absorption, and at the characteristic peak 3426, there is a strong absorption of -CH2-, indicating that the epoxy modification is successful. The epoxy equivalent of the epoxy-modified lignin obtained by further testing with the hydrochloric acid-pyridine method is 0.89 mol / 100 g.

[0050] Example 6

[0051] Into the multifunctional reactor, 30 parts of coffee grounds treated in Example 3, 45 parts of cyclopropylpropionaldehyde, 45 parts of 1,4-dioxane and 5 parts of hydrochloric acid were added in order by mass. The reactants were heated to 100° C. at a stirring speed of 1000 rpm, and the reaction was carried out for 2 hours. The reaction solution was stirred every 30 minutes until the reaction was completed; the mixture was filtered, and then washed with 1,4-dioxane and methanol in turn until the washing liquid was colorless to ensure that the cellulose was completely removed, and the filter residue was collected and dried to obtain crude cyclopropyl modified lignin. The obtained crude cyclopropyl modified lignin was added into a multifunctional reactor, and 1,4-dioxane and cyclopropyl propionaldehyde were added in sequence. The mass ratio of crude cyclopropyl modified lignin, 1,4-dioxane and cyclopropyl propionaldehyde was 10:30:8. Then, NaHCO3 solution was added to neutralize the acid in the filter residue. Then, the mixture was heated to 40°C and the pressure was 55 mbar by vacuum distillation to distill out 1,4-dioxane and collect and store it. The distilled solution was filtered and the filter residue was collected. The filter residue was air-dried at 30°C to obtain purified cyclopropyl modified lignin, and infrared spectroscopy was performed as shown in the following figure. Figure 3 As shown in a, there is no obvious infrared absorption at the characteristic peak 912 and the -CO- bond, while there is a strong absorption at the characteristic peak 3426, i.e. -CH2-, indicating that the cyclopropyl modification is successful.

[0052] The cyclopropyl modified lignin obtained above was added into a multifunctional reactor, and hydrogen peroxide with a concentration of 30 wt% was added, and then sodium hydroxide was added, and the mass ratio of cyclopropyl modified lignin to hydrogen peroxide was 1:3. The pH value of the reaction solution was adjusted to 12, heated to 60 °C, refluxed for 5 hours, filtered, washed with deionized water until the washing solution was neutral, and the filter residue was collected to obtain epoxy modified lignin; the obtained epoxy modified lignin was characterized by infrared spectroscopy as follows Figure 3 As shown in b, at the characteristic peak 912, there is an obvious infrared absorption, and at the characteristic peak 3426, there is a strong absorption of -CH2-, indicating that the epoxy modification is successful. The epoxy equivalent of the epoxy-modified lignin obtained by further testing with the hydrochloric acid-pyridine method is 0.93 mol / 100 g.

[0053] Example 7

[0054] Into the multifunctional reactor, 20 parts of coffee grounds treated in Example 2, 45 parts of cyclopropylbutyraldehyde, 45 parts of 1,4-dioxane and 4 parts of hydrochloric acid were added in order by mass. The reactants were heated to 100° C. at a stirring speed of 700 rpm, and the reaction was carried out for 4 hours. The reaction solution was stirred every 30 minutes until the reaction was completed; filtered, and then washed with 1,4-dioxane and methanol in turn until the washing liquid was colorless to ensure that the cellulose was completely removed, and the filter residue was collected and dried to obtain crude cyclopropyl modified lignin. The obtained crude cyclopropyl modified lignin was added into a multifunctional reactor, and 1,4-dioxane and cyclopropylbutyraldehyde were added in sequence, and the mass ratio of crude cyclopropyl modified lignin, 1,4-dioxane and cyclopropylbutyraldehyde was 10:30:8; then NaHCO3 solution was added to neutralize the acid in the filter residue; then the reduced pressure distillation was heated to 40 °C and the pressure was 65 mbar to distill, 1,4-dioxane was evaporated and collected and stored, the distilled solution was filtered, the filter residue was collected, and the filter residue was air-dried at 30 °C to obtain the purified cyclopropyl modified lignin, and the infrared spectrum was characterized as follows Figure 3 As shown in a, there is no obvious infrared absorption at the characteristic peak 912 and the -CO- bond, while there is a strong absorption at the characteristic peak 3426, i.e. -CH2-, indicating that the cyclopropyl modification is successful.

[0055] The cyclopropyl modified lignin obtained above was added into a multifunctional reactor, and 30 wt% hydrogen peroxide was added, and then sodium hydroxide was added, and the mass ratio of cyclopropyl modified lignin to hydrogen peroxide was 1:6. The pH value of the reaction solution was adjusted to 12, heated to 60 °C, refluxed for 5 hours, filtered, washed with deionized water until the washing solution was neutral, and the filter residue was collected to obtain epoxy modified lignin. The obtained epoxy modified lignin was characterized by infrared spectroscopy as follows: Figure 3 As shown in b, at the characteristic peak 912, there is an obvious infrared absorption, and at the characteristic peak 3426, there is a strong absorption of -CH2-, indicating that the epoxy modification is successful. The epoxy equivalent of the epoxy-modified lignin obtained by further testing with the hydrochloric acid-pyridine method is 0.96 mol / 100 g.

[0056] Example 8

[0057] Into the multifunctional reactor, 20 parts of coffee grounds treated in Example 3, 40 parts of cyclopropylacetaldehyde, 45 parts of 1,4-dioxane and 5 parts of hydrochloric acid were added in order by mass. The reactants were heated to 100° C. at a stirring speed of 1000 rpm, and the reaction was carried out for 4 hours. The reaction solution was stirred every 30 minutes until the reaction was completed; filtered, and then washed with 1,4-dioxane and methanol in turn until the washing liquid was colorless to ensure that the cellulose was completely removed, and the filter residue was collected and dried to obtain crude cyclopropyl modified lignin. The obtained crude cyclopropyl modified lignin was added into a multifunctional reactor, and 1,4-dioxane and cyclopropylacetaldehyde were added in sequence. The mass ratio of crude cyclopropyl modified lignin, 1,4-dioxane and cyclopropylacetaldehyde was 10:20:8. Then, NaHCO3 solution was added to neutralize the acid in the residue. Then, the mixture was heated to 40°C under a pressure of 55 mbar by vacuum distillation to distill out 1,4-dioxane and collect and store it. The distilled solution was filtered and the residue was collected. The residue was air-dried at 30°C to obtain purified cyclopropyl modified lignin, which was characterized by infrared spectroscopy. Figure 3 As shown in a, there is no obvious infrared absorption at the characteristic peak 912 and the -CO- bond, while there is a strong absorption at the characteristic peak 3426, i.e. -CH2-, indicating that the cyclopropyl modification is successful.

[0058] The cyclopropyl modified lignin obtained above was added into a multifunctional reactor, and hydrogen peroxide with a concentration of 20 wt% was added, and then sodium hydroxide was added, and the pH value of the reaction solution was adjusted to 12, heated to 50 °C, refluxed for 4 hours, filtered, washed with deionized water until the washing solution was neutral, and the filter residue was collected to obtain epoxy modified lignin; the mass ratio of the cyclopropyl modified lignin to the hydrogen peroxide was 1:9, and the obtained epoxy modified lignin was characterized by infrared spectroscopy as follows Figure 3 As shown in b, at the characteristic peak 912, there is an obvious infrared absorption, and at the characteristic peak 3426, there is a strong absorption of -CH2-, indicating that the epoxy modification is successful. The epoxy equivalent of the epoxy-modified lignin obtained by further testing with the hydrochloric acid-pyridine method is 0.98 mol / 100 g.

[0059] Example 9

[0060] Into the multifunctional reactor, 20 parts of coffee grounds treated in Example 1, 45 parts of cyclopropylacetaldehyde, 40 parts of 1,4-dioxane and 4 parts of hydrochloric acid were added in order by mass, and the reactants were heated to 95° C. at a stirring speed of 1000 rpm, and reacted for 3 hours, stirring the reaction solution every 30 minutes until the reaction was completed; filtered, and then washed with 1,4-dioxane and methanol in turn until the washing liquid was colorless to ensure that the cellulose was completely removed, and the filter residue was collected and dried to obtain crude cyclopropyl modified lignin. The obtained crude cyclopropyl modified lignin was added into a multifunctional reactor, and 1,4-dioxane and cyclopropylacetaldehyde were added in sequence. The mass ratio of crude cyclopropyl modified lignin, 1,4-dioxane and cyclopropylacetaldehyde was 10:30:8. Then, NaHCO3 solution was added to neutralize the acid in the filter residue. Then, the mixture was heated to 40°C under a pressure of 60 mbar by vacuum distillation to distill out 1,4-dioxane and collect and store it. The distilled solution was filtered and the filter residue was collected. The filter residue was air-dried at 30°C to obtain purified cyclopropyl modified lignin, which was characterized by infrared spectroscopy. Figure 3 As shown in a, there is no obvious infrared absorption at the characteristic peak 912 and the -CO- bond, while there is a strong absorption at the characteristic peak 3426, i.e. -CH2-, indicating that the cyclopropyl modification is successful.

[0061] The cyclopropyl modified lignin obtained above was added into a multifunctional reactor, and a 10 wt% hydrogen peroxide solution was added, and then sodium hydroxide was added, and the pH value of the reaction solution was adjusted to 12, and the reaction solution was heated to 50°C, and refluxed for 5 hours, filtered, and washed with deionized water until the washing solution was neutral, and the filter residue was collected to obtain epoxy modified lignin; the mass ratio of the cyclopropyl modified lignin to the hydrogen peroxide solution was 1:9, and the obtained epoxy modified lignin was characterized by infrared spectroscopy as follows: Figure 3 As shown in b, at the characteristic peak 912, there is an obvious infrared absorption, and at the characteristic peak 3426, there is a strong absorption of -CH2-, indicating that the epoxy modification is successful. The epoxy equivalent of the epoxy-modified lignin obtained by further testing with the hydrochloric acid-pyridine method is 0.85 mol / 100 g.

[0062] Example 10

[0063] Table 1 Raw material ratio of Example 10

[0064]

[0065] The epoxy-modified lignin in Table 1 is the epoxy-modified lignin prepared by the method of Example 4.

[0066] In a multifunctional reactor, deionized water, epoxy-modified lignin, bisphenol A epoxy resin and alkylene glycidyl ether were added in sequence according to the formula weight, nitrogen was introduced, and the mixture was stirred at a speed of 300 rpm for 30 minutes. Then, an epoxy resin emulsifier ZJ-203 was added, the temperature was raised to 100°C, and the stirring was continued for 30 minutes at the same speed to form a stable emulsion. The temperature was lowered to 40°C, GP-type glycerol polyether was added, and the mixture was stirred at a stirring speed of 1000 rpm for 30 minutes. The introduction of nitrogen was stopped. Ethylenediamine and triethylamine were continued to be added, and the mixture was stirred at a stirring speed of 500 rpm for 30 minutes. The temperature was then raised to 100°C and the reaction was carried out for 6 hours. During the reaction, the water vapor generated by evaporation was removed by a water separator. After the reaction was completed, the temperature was lowered to 40°C, and the mixture was stirred at a stirring speed of 3000 rpm for 60 minutes. The mixture was then stirred at a stirring speed of 3000 rpm for 30 minutes. The mixture was stirred at a stirring speed of 1000 rpm for 60 minutes to obtain the water-based lignin-based epoxy resin coating, the raw material ratio of which is shown in Table 1:

[0067] According to GB / T 6739-1996 “Coating Hardness Pencil Test Method”, the strength of the prepared water-based lignin-based epoxy resin coating (cured at 30°C for 3 hours) was tested manually. The test results showed that the film strength was >B.

[0068] The water resistance of the prepared water-based lignin-based epoxy resin coating was tested according to GB / T 1727-1992. After immersion for 48 hours, the water absorption rate was 10.5%.

[0069] The prepared water-based lignin-based epoxy resin coating film (hereinafter referred to as epoxy resin film) (cured at 30 °C for 3 hours) was tested using a UV-Vis-NIR spectrophotometer. The results are as follows: Figure 4 As shown, the epoxy resin film prepared in this example has a small transmittance in the ultraviolet region (200-400 nm), indicating that the epoxy resin film has good anti-ultraviolet performance.

[0070] The UV resistance of the epoxy resin film was tested according to GBT 16422.3-1997. The experiment used a type I fluorescent ultraviolet lamp, model UV-A340, and the exposure method was: radiation exposure at 60.0 ± 3 ° C for 8 hours under the no-light standard, and then exposure at 50.0 ± 3 ° C for 4 hours under the no-light standard. The results showed that the epoxy resin film prepared in this embodiment has good stability under ultraviolet rays.

[0071] Embodiment 11

[0072] Table 2 Ratio of raw materials in Example 11

[0073]

[0074] The epoxy-modified lignin in Table 2 is the epoxy-modified lignin prepared by the method of Example 5.

[0075] In a multifunctional reactor, deionized water, epoxy-modified lignin, glycerol epoxy resin and neopentyl glycol diglycidyl ether were added in sequence according to the formula weight, nitrogen was introduced, and the mixture was stirred at a speed of 500 rpm for 20 minutes. Then, the epoxy resin emulsifier BY-3052 was added, the temperature was raised to 90°C, and the stirring was continued for 45 minutes at the same speed to form a stable emulsion. The temperature was lowered to 45°C, ethylene glycol siloxane was added, and the mixture was stirred at a stirring speed of 1500 rpm for 20 minutes. The nitrogen introduction was stopped; hexamethylenediamine and triethanolamine were continued to be added, and the mixture was stirred at a stirring speed of 800 rpm for 20 minutes. Then, the temperature was raised to 90°C and the reaction was carried out for 8 hours. During this period, the water vapor generated by evaporation was removed by a water separator. After the reaction was completed, the temperature was lowered to 50°C, and the mixture was stirred at a stirring speed of 4000 rpm for 45 minutes. Then, the mixture was stirred at a stirring speed of 400 The mixture was stirred at a stirring speed of 1000 rpm for 45 minutes to obtain the water-based lignin-based epoxy resin coating, the raw material ratio of which is shown in Table 2:

[0076] According to GB / T 6739-1996 “Coating Hardness Pencil Test Method”, the strength of the prepared water-based lignin-based epoxy resin coating (cured at 30°C for 3 hours) was tested manually. The test results showed that the film strength was >B.

[0077] The water resistance of the prepared water-based epoxy resin film was tested according to GB / T 1727-1992. After immersion for 48 hours, the water absorption rate was 11.2%.

[0078] The prepared water-based lignin-based epoxy resin coating film (hereinafter referred to as epoxy resin film) (cured at 30 °C for 3 hours) was tested using a UV-Vis-NIR spectrophotometer. The results are as follows: Figure 4 As shown, the epoxy resin film prepared in this example has a small transmittance in the ultraviolet region (200-400 nm), indicating that the epoxy resin film has good anti-ultraviolet performance.

[0079] The UV resistance of the epoxy resin film was tested according to GBT 16422.3-1997. The experiment used a type I fluorescent ultraviolet lamp, model UV-A340, and the exposure method was: radiation exposure at 60.0 ± 3 ° C for 8 hours under the no-light standard, and then exposure at 50.0 ± 3 ° C for 4 hours under the no-light standard. The results showed that the epoxy resin film prepared in this embodiment has good stability under ultraviolet rays.

[0080] Example 12

[0081] Table 3 Raw material ratio of Example 12

[0082]

[0083] The epoxy-modified lignin in Table 3 is the epoxy-modified lignin prepared by the method of Example 6.

[0084] In a multifunctional reactor, deionized water, epoxy-modified lignin, butene epoxy resin and polypropylene glycol diglycidyl ether were added in sequence according to the formula weight, nitrogen was introduced, and the mixture was stirred at a speed of 800 rpm for 10 minutes. Then, the epoxy resin emulsifier BY-3052 was added, the temperature was raised to 80°C, and the stirring was continued for 30 minutes at the same speed to form a stable emulsion. The temperature was lowered to 50°C, polysiloxane was added, and the mixture was stirred at a stirring speed of 2000 rpm for 10 minutes. The nitrogen introduction was stopped; diethylaminopropylamine and DMP-30 were continued to be added, and the mixture was stirred at a stirring speed of 1000 rpm for 10 minutes. Then, the temperature was raised to 100°C and the reaction was carried out for 6 hours. During this period, the water vapor generated by evaporation was removed by a water separator. After the reaction was completed, the temperature was lowered to 40°C, and the mixture was stirred at a stirring speed of 5000 rpm for 30 minutes. Then, the mixture was stirred at a stirring speed of 5000 rpm for 5 minutes. The mixture was stirred at a stirring speed of 1000 rpm for 30 minutes to obtain the water-based lignin-based epoxy resin coating, the raw material ratio of which is shown in Table 3:

[0085] According to GB / T 6739-1996 “Coating Hardness Pencil Test Method”, the strength of the prepared water-based lignin-based epoxy resin coating (cured at 30°C for 3 hours) was tested manually. The test results showed that the film strength was >B.

[0086] The water resistance of the prepared water-based epoxy resin film was tested according to GB / T 1727-1992. After immersion for 48 hours, the water absorption rate was 12.1%.

[0087] The prepared water-based lignin-based epoxy resin coating film (hereinafter referred to as epoxy resin film) (cured at 30 °C for 3 hours) was tested using a UV-Vis-NIR spectrophotometer. The results are as follows: Figure 4 As shown, the epoxy resin film prepared in this example has a small transmittance in the ultraviolet region (200-400 nm), indicating that the epoxy resin film has good anti-ultraviolet performance.

[0088] The UV resistance of the epoxy resin film was tested according to GBT 16422.3-1997. The experiment used a type I fluorescent ultraviolet lamp, model UV-A340, and the exposure method was: radiation exposure at 60.0 ± 3 ° C for 8 hours under the no-light standard, and then exposure at 50.0 ± 3 ° C for 4 hours under the no-light standard. The results showed that the epoxy resin film prepared in this embodiment has good stability under ultraviolet rays.

[0089] Example 13

[0090] In a multifunctional reactor, deionized water, epoxy-modified lignin, glycerol epoxy resin and 1,4-butanediol diglycidyl ether were added in sequence according to the formula weight, nitrogen was introduced, and the mixture was stirred at a speed of 500 rpm for 20 minutes. Then, BY-3052, an epoxy resin emulsifier, was added, the temperature was raised to 90°C, and the stirring was continued for 45 minutes at the same speed to form a stable emulsion. The temperature was lowered to 45°C, GP-type glycerol polyether was added, and the mixture was stirred at a stirring speed of 1500 rpm for 20 minutes. The introduction of nitrogen was stopped. Methyl polyethylene glycol amine and phenol were continued to be added, and the mixture was stirred at a stirring speed of 800 rpm for 20 minutes. Then the temperature was raised to 90°C and the reaction was carried out for 8 hours. During the reaction, the water vapor generated by evaporation was removed by a water separator. After the reaction was completed, the temperature was lowered to 50°C and the stirring speed was increased to 4000 rpm. The mixture was stirred at a stirring speed of 100 rpm for 45 minutes, and then stirred at a stirring speed of 400 rpm for 45 minutes to obtain the water-based lignin-based epoxy resin coating, the raw material ratio of which is shown in Table 4:

[0091] According to GB / T 6739-1996 “Coating Hardness Pencil Test Method”, the strength of the prepared water-based lignin-based epoxy resin coating (cured at 30°C for 3 hours) was tested manually. The test results showed that the film strength was >B.

[0092] The water resistance of the prepared water-based epoxy resin film was tested according to GB / T 1727-1992. After immersion for 48 hours, the water absorption rate was 10.7%.

[0093] The prepared water-based lignin-based epoxy resin coating film (hereinafter referred to as epoxy resin film) (cured at 30 °C for 3 hours) was tested using a UV-Vis-NIR spectrophotometer. The results are as follows: Figure 4 As shown, the epoxy resin film prepared in this example has a small transmittance in the ultraviolet region (200-400 nm), indicating that the epoxy resin film has good anti-ultraviolet performance.

[0094] The UV resistance of the epoxy resin film was tested according to GBT 16422.3-1997. The experiment used a type I fluorescent ultraviolet lamp, model UV-A340, and the exposure method was: radiation exposure at 60.0 ± 3 ° C for 8 hours under the no-light standard, and then exposure at 50.0 ± 3 ° C for 4 hours under the no-light standard. The results showed that the epoxy resin film prepared in this embodiment has good stability under ultraviolet rays.

[0095] Table 4 Raw material ratio of Example 13

[0096]

[0097] The epoxy-modified lignin in Table 4 is the epoxy-modified lignin prepared by the method of Example 7.

[0098] Embodiment 14

[0099] In a multifunctional reactor, deionized water, epoxy-modified lignin, bisphenol A epoxy resin and hexanediol diglycidyl ether were added in sequence according to the formula weight, nitrogen was introduced, and the mixture was stirred at a speed of 800 rpm for 10 minutes. Then, an epoxy resin emulsifier ZJ-203 was added, the temperature was raised to 80°C, and the stirring was continued for 30 minutes at the same speed to form a stable emulsion. The temperature was lowered to 50°C, polysiloxane was added, and the mixture was stirred at a stirring speed of 2000 rpm for 10 minutes. The introduction of nitrogen was stopped. Ethylenediamine and triethylamine were continued to be added, and the mixture was stirred at a stirring speed of 1000 rpm for 10 minutes. The temperature was then raised to 100°C and the reaction was carried out for 6 hours. During the reaction, the water vapor generated by evaporation was removed by a water separator. After the reaction was completed, the temperature was lowered to 40°C, and the mixture was stirred at a stirring speed of 5000 rpm for 30 minutes. The mixture was then stirred at a stirring speed of 5000 rpm for 5 minutes. The mixture was stirred at a stirring speed of 1000 rpm for 30 minutes to obtain the water-based lignin-based epoxy resin coating, the raw material ratio of which is shown in Table 5:

[0100] According to GB / T 6739-1996 “Coating Hardness Pencil Test Method”, the strength of the prepared water-based lignin-based epoxy resin coating (cured at 30°C for 3 hours) was tested manually. The test results showed that the film strength was >B.

[0101] The water resistance of the prepared water-based epoxy resin film was tested according to GB / T 1727-1992. After immersion for 48 hours, the water absorption rate was 11.7%.

[0102] The prepared water-based lignin-based epoxy resin coating film (hereinafter referred to as epoxy resin film) (cured at 30 °C for 3 hours) was tested using a UV-Vis-NIR spectrophotometer. The results are as follows: Figure 4As shown, the epoxy resin film prepared in this example has a small transmittance in the ultraviolet region (200-400 nm), indicating that the epoxy resin film has good anti-ultraviolet performance.

[0103] The UV resistance of the epoxy resin film was tested according to GBT 16422.3-1997. The experiment used a type I fluorescent ultraviolet lamp, model UV-A340, and the exposure method was: radiation exposure at 60.0 ± 3 ° C for 8 hours under the no-light standard, and then exposure at 50.0 ± 3 ° C for 4 hours under the no-light standard. The results showed that the epoxy resin film prepared in this embodiment has good stability under ultraviolet rays.

[0104] Table 5 Raw material ratio of component A in Example 14

[0105]

[0106] The epoxy-modified lignin in Table 5 is the epoxy-modified lignin prepared by the method of Example 8.

[0107] Embodiment 15

[0108] In a multifunctional reactor, deionized water, epoxy-modified lignin, glycerol epoxy resin and ethylene glycol diglycidyl ether were added in sequence according to the formula weight, nitrogen was introduced, and the mixture was stirred at a speed of 300 rpm for 30 minutes. Then, an epoxy resin emulsifier ZJ-203 was added, the temperature was raised to 100°C, and the stirring was continued for 30 minutes at the same speed to form a stable emulsion. The temperature was lowered to 40°C, polysiloxane was added, and the mixture was stirred at a stirring speed of 1000 rpm for 30 minutes. The nitrogen introduction was stopped. Ethylenediamine and resorcinol were continued to be added, and the mixture was stirred at a stirring speed of 500 rpm for 30 minutes. Then, the temperature was raised to 100°C and the reaction was carried out for 6 hours. During the reaction, the water vapor generated by evaporation was removed by a water separator. After the reaction was completed, the temperature was lowered to 40°C, and the mixture was stirred at a stirring speed of 3000 rpm for 60 minutes. Then, the stirring speed was increased to 3000 rpm for 30 minutes. The mixture was stirred at a stirring speed of 1000 rpm for 60 minutes to obtain the water-based lignin-based epoxy resin coating, the raw material ratio of which is shown in Table 6:

[0109] According to GB / T 6739-1996 “Coating Hardness Pencil Test Method”, the strength of the prepared water-based lignin-based epoxy resin coating (cured at 30°C for 3 hours) was tested manually. The test results showed that the film strength was >B.

[0110] The water resistance of the prepared water-based epoxy resin film was tested according to GB / T 1727-1992. After immersion for 48 hours, the water absorption rate was 12.5%.

[0111] The prepared water-based lignin-based epoxy resin coating film (hereinafter referred to as epoxy resin film) (cured at 30 °C for 3 hours) was tested using a UV-Vis-NIR spectrophotometer. The results are as follows: Figure 4 As shown, the epoxy resin film prepared in this example has a small transmittance in the ultraviolet region (200-400 nm), indicating that the epoxy resin film has good anti-ultraviolet performance.

[0112] The UV resistance of the epoxy resin film was tested according to GBT 16422.3-1997. The experiment used a type I fluorescent ultraviolet lamp, model UV-A340, and the exposure method was: radiation exposure at 60.0 ± 3 ° C for 8 hours under the no-light standard, and then exposure at 50.0 ± 3 ° C for 4 hours under the no-light standard. The results showed that the epoxy resin film prepared in this embodiment has good stability under ultraviolet rays.

[0113] Table 6 Raw material ratio of Example 15

[0114]

[0115] The epoxy-modified lignin in Table 6 is the epoxy-modified lignin prepared by the method of Example 9.

[0116] Technical personnel should note that although the present invention has been described according to the above specific implementation methods, the inventive concept of the present invention is not limited to this invention, and any modification using the inventive concept will be included in the scope of protection of this patent.

Claims

1. A water-based lignin-based epoxy resin coating, characterized in that: The raw materials of the water-based lignin-based epoxy resin coating are, by weight: 30-50 parts of epoxy-modified lignin, 10-20 parts of epoxy polymer, 8-12 parts of epoxy resin curing agent, 0.020-0.030 parts of epoxy resin accelerator, 4-6 parts of emulsifier, 10-20 parts of diluent, 0.5-0.8 parts of defoamer and 80-100 parts of deionized water; the preparation method of the epoxy-modified lignin comprises the following steps: S1 pretreatment: Soak the coffee grounds in n-hexane, with the mass volume ratio of coffee grounds to n-hexane being 5-10 g:1-10 mL, react at 20-30 °C and a mechanical stirring speed of 200-500 rpm for 3-6 hours, filter and remove the filtrate to obtain the coffee grounds after impurities are removed; S2 Cyclopropyl modification of lignin: add 20-30 parts of coffee grounds treated with S1, 35-45 parts of cyclopropyl hydrocarbon aldehyde, 35-45 parts of 1,4-dioxane and 2-5 parts of hydrochloric acid to a multifunctional reactor in order by mass to obtain a reactant, heat the reactant to 90-100 °C at a stirring speed of 500-1000 rpm, react for 2-4 hours, stir every 30 minutes until the reaction is completed; filter, then wash with 1,4-dioxane and methanol in turn until the washing liquid is colorless to ensure that the cellulose is completely removed, collect the filter residue, dry it, and obtain crude cyclopropyl modified lignin; S3 Collection and purification of cyclopropyl modified lignin: The crude cyclopropyl modified lignin obtained in S2 is added to a multifunctional reactor, and 1,4-dioxane and cyclopropyl aldehyde are added in sequence, and then a NaHCO3 solution is added to neutralize the acid in the filter residue; then, the mixture is heated to 30-40°C and distilled at a pressure of 55-65 mbar to evaporate 1,4-dioxane and collect and store it, the distilled solution is filtered, the filter residue is collected, and the filter residue is air-dried at 30°C to obtain purified cyclopropyl modified lignin; wherein the mass ratio of crude cyclopropyl modified lignin, 1,4-dioxane and cyclopropyl aldehyde is 10:20-30:6-8; S4 Epoxy modification of lignin: Add the purified cyclopropyl-modified lignin obtained in S3 into a multifunctional reactor, add hydrogen peroxide with a concentration of 10 wt%~30 wt%, then add sodium hydroxide, adjust the pH value of the reaction solution to 10~12, heat to 50~60°C, reflux for 3~5 hours, filter, wash with deionized water until the washing solution is neutral, collect the filter residue, and obtain epoxy-modified lignin; the mass ratio of the purified cyclopropyl-modified lignin to hydrogen peroxide is 1:3~9.

2. The water-based lignin-based epoxy resin coating according to claim 1, characterized in that: The cyclopropyl hydrocarbon aldehyde in S2 is at least one of cyclopropyl acetaldehyde, cyclopropyl propionaldehyde and cyclopropyl butyraldehyde.

3. The water-based lignin-based epoxy resin coating according to claim 1, characterized in that: The cyclopropyl hydrocarbon aldehyde in S3 is at least one of cyclopropyl acetaldehyde, cyclopropyl propionaldehyde and cyclopropyl butyraldehyde.

4. The water-based lignin-based epoxy resin coating according to claim 1, characterized in that: The epoxy polymer is at least one of bisphenol A epoxy resin, glycerol epoxy resin and butene epoxy resin.

5. The water-based lignin-based epoxy resin coating according to claim 1, characterized in that: The epoxy resin curing agent is at least one of methyl polyethylene glycol amine, ethylenediamine, hexamethylenediamine, diethylaminopropylamine, dicyandiamide, and phthalic anhydride.

6. The water-based lignin-based epoxy resin coating according to claim 1, characterized in that: The epoxy resin accelerator is at least one of DMP-30, triethylamine, triethanolamine, phenol and resorcinol.

7. The water-based lignin-based epoxy resin coating according to claim 1, characterized in that: The diluent is at least one of alkylene glycidyl ether, 1,4-butanediol diglycidyl ether, ethylene glycol diglycidyl ether, polypropylene glycol diglycidyl ether, 1,6-hexanediol diglycidyl ether, neopentyl glycol diglycidyl ether, and hexanediol diglycidyl ether.

8. The water-based lignin-based epoxy resin coating according to claim 1, characterized in that: The emulsifier is at least one of the epoxy resin emulsifier ZJ-203 and the epoxy resin emulsifier BY-3052.

9. The water-based lignin-based epoxy resin coating according to claim 1, characterized in that: The defoaming agent is at least one of polysiloxane, GP type glycerol polyether and ethylene glycol siloxane.

10. A method for preparing a water-based lignin-based epoxy resin coating, for preparing the water-based lignin-based epoxy resin coating as claimed in any one of claims 1 to 9, the preparation method comprising the following steps: a. In a multifunctional reactor, deionized water, epoxy-modified lignin, epoxy polymer and diluent are added in sequence according to the formula weight, nitrogen is introduced, and stirring is performed at a speed of 300-800 rpm for 10-30 minutes, then an emulsifier is added, the temperature is raised to 80-100 °C, stirring is continued at the same speed for 30-60 minutes to form a stable emulsion, the temperature is lowered to 40-50 °C, a defoamer is added, stirring is performed at a stirring speed of 1000-2000 rpm for 10-30 minutes, and the introduction of nitrogen is stopped; b. Continue to add epoxy resin curing agent and epoxy resin accelerator according to the formula amount, stir at a stirring speed of 500-1000 rpm for 10-30 minutes, then raise the temperature to 80-100 ° C, react for 6-10 hours, during which time use a water separator to remove water vapor generated by evaporation. After the reaction is completed, cool to 40-60 ° C, stir at a stirring speed of 3000-5000 rpm for 30-60 minutes, and then stir at a stirring speed of 300-500 rpm for 30-60 minutes to obtain the water-based lignin-based epoxy resin coating.

Citation Information

Patent Citations

  • A method for modifying lignin and a method for preparing lignin-based epoxy resin

    CN109467716B

  • Waterproof lignin-based epoxy resin adhesive and preparation method thereof

    CN112126391A

  • Lignin-based epoxy resin coating based on pulping black liquor and preparation method of lignin-based epoxy resin coating

    CN115141356A

  • Lignin-based waterborne polyurethane and preparation method thereof

    CN115386063A